Unveiling the creep mechanisms of rare earth element yttrium added and SPS consolidated CoCrFeNi high entropy alloys - Tekin, Mustafa; Kotan, Hasan; Baydogan, Murat; Kaba, Mertcan; Balci, Erdem; Bayrak, Kubra Gurcan; Ayas, Erhan (Walter De Gruyter Gmbh, 2025)
As high entropy alloys (HEAs) continue to be increasingly studied for next-generation structural materials, gaining a comprehensive understanding of their mechanical properties, including their creep behaviors, remains essential. In this work, rare earth element yttrium (Y) added CoCrFeNi HEAs are produced by mechanical alloying, followed by consolidation via spark plasma sintering (SPS) with ultrafine grain sizes. The microstructures after SPS consolidation are examined using X-ray diffraction (XRD) and transmission electron microscopy (TEM). The creep properties, including creep displacement, creep strain rate, creep stress, and stress exponent, are evaluated using a nanoindentation test with a Berkovich tip indenter. The results reveal that the average grain size of CoCrFeNi HEA is determined to be 385 +/- 65 nm after SPS consolidation, which reduces to 190 +/- 30 nm and 155 +/- 55 nm with 1 and 4 at.% Y additions, respectively. Accordingly, HEA with the addition of 4 at.% Y exhibits increased hardness, attributed to the presence of additional Y-based oxides and the reduced grain size in its microstructure. Furthermore, the creep mechanisms for the investigated CoCrFeNi HEAs are primarily dominated by dislocation-precipitation interaction based on the calculated stress exponent values.
Keywords: creep mechanism; high entropy alloys; mechanical alloying; nanoindentation creep; spark plasma sintering; stress exponent